Pharmacological inhibition of IRAK1 and IRAK4 prevents endothelial inflammation and atherosclerosis in ApoE-/- mice. (January 2022) - Wu, Xiumei; Xu, Mengyun; Liu, Zhenghong; Zhang, Zhidan; Liu, Yujie; Luo, Sihui; Zheng, Xueying; Little, Peter J.; Xu, Suowen; Weng, Jianping
Abstract: Inflammation associated endothelial dysfunction represents a pivotal contributor to atherosclerosis. Increasingly, evidence has demonstrated that interleukin 1 receptor (IL1-R) / toll-like receptor (TLR) signaling participates in the development of atherosclerosis. Recent large-scale clinical trials have supported the therapeutic potential of anti-inflammatory therapies targeting IL-1β and IL-6 in reducing atherosclerosis. The present study examined the pharmacological effects of IL-1R-associated kinase 1 and 4 inhibitors (IRAK1/4i) in regulating inflammation of the endothelium and atherosclerosis. We demonstrate that dual pharmacological inhibition of IRAK1 and IRAK4 by an IRAK1/4i is more effective against LPS induced endothelial inflammation, compared with IRAK1 inhibitor or IRAK4 inhibitor monotherapy. IRAK1/4i showed little endothelial cell toxicity at concentrations from 1 μM up to 10 μM. Inhibition of IRAK1/4 reduced endothelial activation induced by LPS in vitro as evidenced by attenuated monocyte adhesion to the endothelium. Mechanistically, blockade of IRAK1/4 ameliorated the transcriptional activity of NF-κB. To assess the pharmacological effects of IRAK1/4i on atherosclerosis in vivo, ApoE -/- mice were orally administered IRAK1/4i (20 mg/kg/d) for 8 weeks. We show that IRAK1/4i reduced atherosclerotic lesion size in the aortic sinus and increased hepatic LDLR protein levels as well as lowered LDL-C level, without affecting other lipid parameters or glucose tolerance. Taken together, our findings demonstrate that dual pharmacological inhibition of IRAK1 and IRAK4 attenuates endothelial inflammation, lowers LDL-C levels and reduces atherosclerosis. Our study reinforces the evolving standing of anti-inflammatory approaches in cardiovascular therapeutics. Graphical Abstract: ga1